The Truth in History (Iter, 2022)
In this article we want to explain the special relationship between Historyant the Truth in the historical studies. We want to point up the relevanceo f this concept for historians who always are looking for a “historicaltruth ” in their researches. However, many times, they do not consider themethodological problems o f this enuncíate.
Keywords: Historical Truth, positivism, historical objectivity, subjectivity, historicism